The Use of Avatars in Gender Segregated Online Learning Within MOOCs in Saudi Arabia - A Rwaq Case Study - Adham, Raniah; Parslow, Pat; Dimitriadi, Yota; Lundqvist, Karsten Øster (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2018)
In Saudi Arabia, gender-segregation is a known issue within higher education that often deprives female tutors from providing online learning and Massive Open Online Courses (MOOCs). As well, students may not be getting the benefit of their experience and teaching. The purpose of this study is to develop an Avatar tool to represent a female tutor in a MOOC course with the aim of alleviating the issues of a gender-segregated society in online learning. This project will undertake and analyse a case study concerning the experience of females teaching a MOOC course on “Rwaq” the first Saudi Arabian platform, which was launched in September 2013. The literature on gender-segregation and education technology is reviewed. As an example, gender-segregated in higher education and online learning in Saudi Arabia, Virtual Learning Environments (VLE), Avatar technology in higher education, and finally the adoption of an Avatar tool in MOOCs platforms in SA are examined. One of the objectives of the study is to develop a social interaction environment with learners in online learning within MOOCs. The ultimate objective of this study is to examine if this Avatar tool could alleviate issues of gender-segregation for female lecturers in online learning courses within MOOCs in higher education in Saudi Arabia.